2016
DOI: 10.4103/0972-5229.186219
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and mortality of elderly patients admitted to the Intensive Care Unit of a district hospital

Abstract: Aim:To study all the elderly patients (≥75 years) who were admitted in an Intensive Care Unit (ICU) of a Spanish hospital and identify factors associated with mortality.Patients and Methods:A retrospective, observational data collected prospectively in patients ≥75 years recruited from the ICU in the period of January 2004 to December 2010.Results:During the study period, 1661 patients were admitted to our unit, of whom 553 (33.3%) were older than 75 years. The mean age was 79.9 years, 317 (57.3%) were male, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 34 publications
7
21
1
3
Order By: Relevance
“…Most of these, like in the present study, also entered through the emergency service. (2) In addition, in another study, sepsis had an impact on the mortality of elderly patients hospitalized at an ICU, regardless of the length of hospital stay. (11) Hence, it is observed that the clinical demands of the long-living patients in the ICU stand out in comparison to the surgical demands, possibly due to the worsening of chronic problems.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Most of these, like in the present study, also entered through the emergency service. (2) In addition, in another study, sepsis had an impact on the mortality of elderly patients hospitalized at an ICU, regardless of the length of hospital stay. (11) Hence, it is observed that the clinical demands of the long-living patients in the ICU stand out in comparison to the surgical demands, possibly due to the worsening of chronic problems.…”
Section: Discussionmentioning
confidence: 94%
“…(6) This result, however, diverges from other studies that indicate a prevalence of hospitalizations of male patients, justified by the fact that men are more negligent with their health and are at greater risk of clinical decompensation. (2,(7)(8)(9) Most of the long-living patients came to the ICU for the emergency unit. Their most prevalent comorbidities were hypertension, diabetes and other heart diseases, with hypertension and diabetes being present in the majority.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations